2018
DOI: 10.1002/ijgo.12594
|View full text |Cite
|
Sign up to set email alerts
|

HPV knowledge, vaccine knowledge, and vaccine acceptance in women with cervical cytology anomalies attending colposcopy clinics in Puerto Rico

Abstract: Knowledge of HPV and HPV vaccine(s) was high, but vaccine uptake was low in the study population. Physicians' active roles in HPV education and vaccination are crucial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…As the knowledge of HPV and its vaccine is pivotal for HPV vaccine promotion , identifying the factors associated with awareness thereof is vital to effectively to raise awareness about HPV infection and the benefits of HPV vaccination among targeted populations. We identified predictors of HPV and HPV vaccine awareness that were concordant with findings reported in previous studies, namely age , education level , income level , age at sexual debut and number of sexual partners . Being the mother of a daughter was also associated with high HPV awareness .…”
Section: Discussionsupporting
confidence: 86%
“…As the knowledge of HPV and its vaccine is pivotal for HPV vaccine promotion , identifying the factors associated with awareness thereof is vital to effectively to raise awareness about HPV infection and the benefits of HPV vaccination among targeted populations. We identified predictors of HPV and HPV vaccine awareness that were concordant with findings reported in previous studies, namely age , education level , income level , age at sexual debut and number of sexual partners . Being the mother of a daughter was also associated with high HPV awareness .…”
Section: Discussionsupporting
confidence: 86%
“…A total of 25.7 % of questionnaire respondents answered that they were in favor of the HPV vaccine, representing a far more negative impression relative to other vaccines, which is the case in other countries [35] , [36] , [37] . As in the previous report [50] , [51] , positive vaccine impressions significantly affected parents’ decision to provide vaccines for their infants in our study ( p < 0.001). However, for the HPV vaccine, parents felt that they had understood the information about this vaccine comprehensively and still had a negative attitude toward vaccination against HPV based on the results of this survey.…”
Section: Discussionsupporting
confidence: 84%
“…As M. Grandahl et al implied, we conclude that a better understanding and impression of routine vaccination programs and other vaccines would positively affect the recovery of HPV vaccine coverage according to our analysis. To improve overall public health, specifically, that of the children, researchers and physicians are key players who have to provide more accurate, convincing, and comprehensive evidence about the HPV vaccine [50] , [51] , [59] , and we should also strive to improve education on other vaccines within the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Ten studies found higher rates of HPV vaccination among higher income patients53–62; 7 studies found higher rates of vaccination for lower income patients63–69; and 12 studies found income was not associated with vaccination rates 43 70–80. Patients with higher income had increased HPV-related awareness50 81–87 and greater rates of provider recommendation 57. Patients with lower income had lower rates of HPV testing88 89 and greater prevalence of HPV infections 23 25 28.…”
Section: Resultsmentioning
confidence: 99%